More answers

Lvl 2

Bb

Q: Simplify 5xsquared plus 14x 3 xsquared 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5x^2 + 14x - 3x^2 - 9 = 2x^2 + 14x - 9

You can expand the first expression in parentheses, then add or subtract like terms.

If you mean: x squared -14x +45 then when factored it is (x-9)(x-5)

-x - 2 + 15x = 14x - 2 = 2(7x - 1)

2x2+14x

Related questions

5x^2 + 14x - 3x^2 - 9 = 2x^2 + 14x - 9

It is 14x+4 simplified

You can expand the first expression in parentheses, then add or subtract like terms.

If you mean: x squared -14x +45 then when factored it is (x-9)(x-5)

-x - 2 + 15x = 14x - 2 = 2(7x - 1)

-x2+14x=49

14x + 11

2x2+14x

(x2 + 14x + 49) = (x + 7)2

14x(x + 2)

x2 + 14x + 48 = (x + 8)(x + 6)

14x+7y=-9